Inflation-induced liquidity constraints in real estate financing - Andrea Gubitz; Karl-Heinz Toedter; Gerhard Ziebarth (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2024)
Despite the "interest rate turnaround" initiated by the ECB in the second half of 2022 as a late reaction to the clearly underestimated persistence of high inflation rates in the euro area, real interest rates are by no means to be regarded as restrictive, neither in the ex post nor in the ex ante view. However, banks have been quite quick to adopt stricter lending guidelines, and demand in housing construction and mortgage lending has plummeted. Against this background, the paper discusses the importance of cash flow effects in annuity loans and in particular analyses the so-called front-loading effect. Accordingly, even if inflation rates are fully anticipated and real market and lending interest rates remain unchanged, higher nominal rates lead to strong additional financial burdens in the first phases of the typically mortgages with long maturities. Such liquidity effects can severely reduce the ability or willingness to pay of private investors in the household sector. This is particularly true for long-run loans in the form of a percentage annuity, as an additional maturity shortening effect occurs here. These types of fixed term loans are quite popular in Germany. Looking ahead, there is also a real risk to the stock of housing loans if there is a refinancing of the large stock of cheap housing loans, a risk that also has implications for macroeconomic and financial stability. – – Trotz der von der EZB eingeleiteten "Zinswende" in der zweiten Jahreshälfte 2022 als späte Reaktion auf die deutlich unterschätzte Persistenz hoher Inflationsraten im Euroraum sind die Realzinsen sowohl in der ex post Betrachtung als auch in der ex ante Betrachtung keineswegs als restriktiv einzuschätzen. Die Banken haben allerdings recht rasch strengere Vergaberichtlinien beschlossen, und die Nachfrage im Wohnungsbau und bei den Hypothekarkrediten ist stark eingebrochen. Der Beitrag thematisiert vor diesem Hintergrund die Bedeutung von Zahlungsstromeffekten bei Annuitätenkrediten und analysiert hier vor allem den sog. front-loading Effekt. Danach führen höhere Nominalzinsen selbst bei vollständig antizipierten Inflationsraten und unveränderten Realzinsen zu starken finanziellen Zusatzbelastungen in den ersten Phasen der typischerweise langen Kreditlaufzeit. Derartige Liquiditätseffekte können die Zahlungsfähigkeit bzw. die Zahlungsbereitschaft der privaten Investoren empfindlich verringern. Dies gilt vor allem bei Darlehen in Form der Prozentannuität, da hier zusätzlich ein Laufzeitenverkürzungseffekt auftritt. Solche Darlehen sind in Deutschland recht populär. Mit Blick auf die Zukunft besteht auch eine reale Gefahr für den Bestand an Wohnungsbaukrediten, wenn es zu einer Refinanzierung des großen Bestands an günstigen Wohnungsbaukrediten kommt, ein Risiko, das auch Auswirkungen auf die makroökonomische und finanzielle Stabilität hat.
Keywords: G21; G51; E59; 330; ECB; monetary policy; liquidity effects of interest rate policy; front loading effects; housing finance; mortgage